The Effectiveness of Repetitive Transcranial Magnetic Stimulation and Theta Burst Stimulation on Selective Attention, Working Memory and Response Time in Suicide - Mahjoubeh Rahimi Doab; Mohammad-Reza Zarindast; Mohammad Nasehi; Mehdi Talebi; Peyman Hassani Abharian (Frontiers in Biomedical Technologies, 2022)
Purpose: Cognitive dysfunction is common in individuals with depression and these cognitive deficits may be associated with a risk of suicide. Therefore, the identification of the cognitive functions of depressed patients and the introduction of effective interventions on these factors are highly important. This study aimed to compare the effectiveness of repetitive Transcranial Magnetic Stimulation (rTMS) and Theta Burst Stimulation (TBS) to improve selective attention, working memory, and response time of depressed individuals with and without a history of suicide.